AKTIVITAS HARIAN ANAK ORANGUTAN (Pongo pygmaeus) DI PUSAT REHABILITASI SINTANG ORANGUTAN CENTER KALIMANTAN BARAT - Achmad Edi Saputra Edi; Hari Prayogo; hafiz Ardian (Universitas Tanjungpura, 2023)
Indonesia is a country that is abundant with high biodiversity, has various types of fauna that are unique and one of them is the primate species, namely the orangutan (Pongo pygmaeus). Orangutans use tree branches to move from one tree to another. The activities of confiscated orangutans are usually held in captivity or from illegal trade. If they are kept in a cage for too long, it will affect the behavior patterns of these orangutans, because they are usually placed in relatively narrow cages, with no trees to climb on. The Sintang Orangutan Center (SOC) is one of the institutions that carries out rescue actions for orangutans either obtained from captivity or from trade illegal. This study aims to record the daily activities of the Bornean orangutan (Pongo pygmaeus) who are in the Sintang Orangutan Center rehabilitation center. Observation of orangutan behavior is carried out using the method focal animal sampling or by observing and recording the behavior of an individual over a period of time provided that the individual is always visible. Behavioral data collection uses the